Aggressive pituitary tumours and carcinomas: two sides of the same coin?. Issue 6 (June 2018) - Trouillas, Jacqueline; Burman, Pia; McCormack, Ann; Petersenn, Stephan; Popovic, Vera; Dekkers, Olaf; Raverot, Gerald
Abstract : The European Society of Endocrinology (ESE) survey reported on the largest cohort of 125 aggressive pituitary tumours (APT) and 40 pituitary carcinomas (PC). Whilst the survey focused on treatment effectiveness, all pathological data were not explored in detail. Here, we comment on some interesting pathological findings, notably the difference between APT and PC.